Political leadership in democracies: some lessons for business? - Butcher, David; Clarke, Martin (Emerald Group Publishing Limited, 2006)
The purpose of this paper is to show that, with demands from a widening range of stakeholders for more democratic approaches to governance, there is an evident need to develop alternative models of organizing. In seeking to understand how to conceptualise this alternative, an analysis of the organizational and political institutional contexts for leadership is provided.